Peran Penggunaan Gawai Terhadap Perkembangan Kognitif Anak Usia Dini (Analisis Systematic Literature Review) - -, Dwi Asalia Nurita (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
This study aims to find out the use of devices in early childhood and find out the effect on cognitive development of children. This research is a literature study with the design of SLR (Systematic Literature Review) using the PRISMA method. Articles are collected by searching through Google Scholar, Garuda.ristekbrin, and ScienceDirect. In conducting searches on databases using keywords: gadgets, gadgets, early childhood, and cognitive development. Only articles that have full text will be included in this review. From the collection obtained 7 articles that are relevant to the title of the study. After that the data is analyzed with content analysis techniques that include several procedures, namely the determination of the analysis unit, the determination of samples and the recording of data. The results of the study found that in their use, devices are known to have a role for children's cognitive development in terms of the intensity of use and applications used. Use with low intensity and the use of educational applications then the device has a positive role in the form of sharpening children's creativity, can develop children's symbolic thinking and can develop children's imagination. While the use of gadgets with non-educational applications and high intensity, the device has a negative role that can reduce the child's concentration and can hinder the exploration of children.